2005
DOI: 10.1128/jcm.43.9.4434-4440.2005
|View full text |Cite
|
Sign up to set email alerts
|

Seminational Surveillance of Fungemia in Denmark: Notably High Rates of Fungemia and Numbers of Isolates with Reduced Azole Susceptibility

Abstract: The aim of this study was to present the first set of comprehensive data on fungemia in Denmark including the distribution of species and range of susceptibility to major antifungal compounds based on a seminational surveillance study initiated in 2003. The catchment area of the participating hospitals had a population of 2.8 million, or 53% of the Danish population. A total of 303 episodes of fungemia were registered (annual rate, 11 of 100,000 people or 0.49 of 1,000 hospital discharges). Candida species acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
2
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 23 publications
(32 reference statements)
6
94
2
12
Order By: Relevance
“…to this chemotherapeutic reported elsewhere [5,6,10,11]. Falagas et al [13] observed high effectiveness of caspofungin -a new echinocandin exhibiting lower toxicity in comparison to amphotericin B, in the treatment of patients with fungal infections caused mainly by Candida spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to this chemotherapeutic reported elsewhere [5,6,10,11]. Falagas et al [13] observed high effectiveness of caspofungin -a new echinocandin exhibiting lower toxicity in comparison to amphotericin B, in the treatment of patients with fungal infections caused mainly by Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…strains isolated from different clinical materials to antifungal agents have been published widely [5][6][7][8][9][10][11][12][13]. However, data concerning the susceptibility of clinical yeast isolates both to antifungal drugs and fungicidal agents used for disinfection and antisepsis procedures are limited.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that Candida guilliermondii caused candidemia in 19 % of examined patients with the prevalence in those suffering from haematological malignancies (9). In addition, it is known that Candida albicans and Cryptococus neoformans can cause general infection, especially in imunocompromised people (5,6,10,11). Similar to our study, Limin et al (12) also found the highest number of Candida isolates in unpasteurised apple juice.…”
Section: Methodsmentioning
confidence: 99%
“…In the hospital environment, fungi can reach blood through various pathways such as catheters or directly from the gastrointestinal tract (5). A Danish epidemiological study demonstrated that Candida albicans caused fungemia in 63 % of clinical patients, while C. krusei was detected only in 3 % of patients (6).…”
mentioning
confidence: 99%
“…They are yeast like fungus that are commensals in healthy humans but can cause systemic infections in immunocompromised individuals [6]. Incidence of fungal infections has led to increased antimicrobial resistance hence making a few antifungal agents active [7,8]. There has been an increase in resistance by Candida albicans to conventionally produced antimicrobials recently, leading to the search of a new antifungal agent [9,10].…”
Section: Introductionmentioning
confidence: 99%